2010
DOI: 10.1186/1471-2148-10-189
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome phylogeny of the subfamily Pitheciinae (Platyrrhini, Primates) by classic cytogenetics and chromosome painting

Abstract: BackgroundThe New World monkey (Platyrrhini) subfamily Pitheciinae is represented by the genera Pithecia, Chiropotes and Cacajao. In this work we studied the karyotypes of Pithecia irrorata (2n = 48) and Cacajao calvus rubicundus (2n = 45 in males and 2n = 46 in females) by G- and C-banding, NOR staining and chromosome painting using human and Saguinus oedipus whole chromosome probes. The karyotypes of both species were compared with each other and with Chiropotes utahicki (2n = 54) from the literature.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…These analyses indicate that the chromosomal differences found among these three taxa are consequences of centric fusions and fissions, pericentric and paracentric inversions, tandem fusions and a Y-autosome translocation; furthermore, these three species are linked by the 2a/10b human association, and Chiropotes and Cacajao are linked by a fission of the ancestral New World association 5/7a (giving association 5a/7a and synteny 5b) and by a fusion leading to the association of human synteny 20/15a/ 14 (Figure 2(c)). It should be noted that the 5/7a fission in pitheciide species and in Atelidae is a homoplasy since it has already been shown that they have different breakpoints (De Oliveira et al 2005;Finotelo et al 2010). In addition, an inversion of the human association 10a/16a has been found in Chiropotes, Pithecia and Cacajao through G banding data analysis; this result apparently is a synapomorphic feature linking all pithecids (including Callicebus) (Finotelo et al 2010), so this association is worthy of further investigation in order to test whether the same breakpoints are shared by the different species.…”
Section: Pitheciidae Familymentioning
confidence: 99%
See 2 more Smart Citations
“…These analyses indicate that the chromosomal differences found among these three taxa are consequences of centric fusions and fissions, pericentric and paracentric inversions, tandem fusions and a Y-autosome translocation; furthermore, these three species are linked by the 2a/10b human association, and Chiropotes and Cacajao are linked by a fission of the ancestral New World association 5/7a (giving association 5a/7a and synteny 5b) and by a fusion leading to the association of human synteny 20/15a/ 14 (Figure 2(c)). It should be noted that the 5/7a fission in pitheciide species and in Atelidae is a homoplasy since it has already been shown that they have different breakpoints (De Oliveira et al 2005;Finotelo et al 2010). In addition, an inversion of the human association 10a/16a has been found in Chiropotes, Pithecia and Cacajao through G banding data analysis; this result apparently is a synapomorphic feature linking all pithecids (including Callicebus) (Finotelo et al 2010), so this association is worthy of further investigation in order to test whether the same breakpoints are shared by the different species.…”
Section: Pitheciidae Familymentioning
confidence: 99%
“…It should be noted that the 5/7a fission in pitheciide species and in Atelidae is a homoplasy since it has already been shown that they have different breakpoints (De Oliveira et al 2005;Finotelo et al 2010). In addition, an inversion of the human association 10a/16a has been found in Chiropotes, Pithecia and Cacajao through G banding data analysis; this result apparently is a synapomorphic feature linking all pithecids (including Callicebus) (Finotelo et al 2010), so this association is worthy of further investigation in order to test whether the same breakpoints are shared by the different species.…”
Section: Pitheciidae Familymentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular cytogenetic methods, including chromosome painting, have been used to compare karyotypes to find chromosomal homologies that may be used for phylogenetic reconstruction of the Platyrrhini [Richard et al, 1996;Neusser et al, 2001;De Oliveira et al, 2002;Ruiz-Herrera et al, 2005;Amaral et al, 2008;Finotelo et al, 2010]. To date, however, only 3 Callicebus species have been investigated by painting methods: C. pallescens with 2 different karyotypes [Stanyon et al, 2000;Barros et al, 2003;Dumas et al, 2005], C. lugens [Stanyon et al, 2003] and C. cupreus [Dumas et al, 2005].…”
mentioning
confidence: 99%
“…The different positions of the probe signal in the two lineages can be explained as the result of a large pericentromeric inversion or of the occurrence of a Figure 2. We considered the literature regarding Strepsirrhini (Müller et al 1997;Richard et al 2000;Cardone et al 2002;Stanyon et al 2002Stanyon et al , 2006Warter et al 2005;Nie et al 2006;Rumpler et al 2008), Platyrrhini (Consigliere et al 1996(Consigliere et al , 1998Richard et al 1996;Morescalchi et al 1997;Stanyon et al 2000Stanyon et al , 2001Stanyon et al , 2003Stanyon et al , 2004Neusser et al 2001;Garcia et al 2002, De Oliveira et al 2002, 2005Barros et al 2003;Serreau et al 2004;Dumas et al 2005Dumas et al , 2007Ruiz-Herrera et al 2005;Amaral et al 2008;Finotelo et al 2010), and Catarrhini Wienberg et al 1992;Bigoni, Koehler, Stanyon, Ishida, et al 1997;Bigoni, Koehler, Stanyon, Morescalchi, et al 1997;Nie et al 1998;Finelli et al 1999;Nie et al 2001;Ruiz-Herrera et al 2002;Müller et al 2003;Bigoni et al 2003Bigoni et al , 2004Stanyon et al 2005;Moulin et al 2008) in order to reconstruct the hy...…”
Section: Marker Order Along Synteny 4 In Primatesmentioning
confidence: 99%